Concrete capable of resisting erosion of carbon-sulfur-silicon-calcium-type sulfate and preparation method of concrete
By combining dense-hydrophobic materials, calcined anionic layered compounds and fibers in concrete, the 'resistance-slow-delay' resistance technology is achieved, and the problem of insufficient corrosion resistance of concrete to carbon-sulfur silicate type sulfate in the prior art is solved, significantly improving resistance and avoiding environmental pollution.
Patent Information
- Application Number
- CN202411709807.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art has limited effects when improving the resistance of concrete to corrosion by carbon-sulfur silicate sulfate, and may cause early strength insufficient, increased risk of cracking and environmental protection problems.
By reasonably combining compact-hydrophobic materials, calcined anionic layered compounds and fibers, a systematic erosion-resistant technology of "resistance-relay" is achieved, which prevents the invasion of SO42- and CO32-, alleviates their reaction with cement hydration products, and prolongs the mechanical attenuation of non-cemented products on concrete caused by carbon-sulfur silicate sulfate erosion.
The resistance of concrete to carbon-sulfurite-type sulfate corrosion is significantly improved, preventing premature deterioration and environmental pollution problems, and long-term resistance to erosion is exerted through phased means.
Smart Images

Figure BDA0005155377200000021 
Figure BDA0005155377200000031 
Figure BDA0005155377200000051
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete anti-corrosion, and in particular relates to concrete resistant to erosion by calcite-type sulfate, and a preparation method thereof. Background Art
[0002] Concrete sulfate attack (TSA) is caused by sulfate or SO4 in the environment. 2- It penetrates into the concrete to form salt crystals, or reacts chemically with some solid components of the hydration product to generate some insoluble salts. The salt crystals or insoluble salts formed absorb a large amount of water to expand in volume, forming expansion internal stress. When the expansion internal stress exceeds the tensile strength of the concrete, it will lead to the destruction of the concrete; in addition, the chemical reaction can also dissolve or decompose components such as CH and CSH in the hardened cement, resulting in the loss of concrete strength and bonding properties.
[0003] In a cold and humid environment (ambient temperature below 15°C), if SO4 2- and CO3 2- Both exist. CSH gel will deteriorate to form calcium-sulfur silicate (CaCO3·CaSO4·CaSiO2·15H2O), which is an expansive product. Although the erosion process of calcium-sulfur silicate is very slow, it directly transforms the CSH phase, the main bonding material in cement paste, into a muddy substance without bonding ability, so it is more destructive. Calcium-sulfur silicate causes cracks, bulges and protrusions on the surface of concrete, making the concrete soft and reducing its strength. In 1965, the American Highway Research Committee first reported a case of concrete being corroded by calcium-sulfur silicate. Subsequently, engineering examples of calcium-sulfur silicate corrosion such as submarine tunnels, bridge pile foundations, and dams were discovered in Europe, America, North America, and South America. Due to the formation of calcium-sulfur silicate without bonding force and the exhaustion of CSH gel, which plays a major bonding role in cement paste, the concrete becomes muddy and loses strength, eventually leading to the collapse of the concrete structure. Therefore. It is urgent to pay enough attention to the resistance of concrete structure to calcium-sulfur silicate-type sulfate corrosion.
[0004] Although there are some technologies for improving the resistance of concrete to calcite sulfate erosion, the current technologies still have many shortcomings: (1) Mineral admixtures. Usually, an appropriate amount of mineral admixtures (fly ash, mineral powder, kaolin, silica fume, etc.) is added to concrete to reduce the effective porosity and most probable pore size of concrete during cement hydration, optimize the pore structure, and effectively reduce the transmission of sulfate ions. However, the use of mineral admixtures alone not only has limited effect on inhibiting the resistance of concrete to calcite sulfate erosion, but may also cause insufficient early strength and increase the risk of cracking. (2) Barium salt TSA inhibitors. Barium salts can combine with SO4 required to generate calcite.2- , generating insoluble BaSO4, thereby reducing the degree of carbon-sulfur calcium silicate sulfate corrosion in concrete. For example, Chinese patent CN 107324681A discloses a carbon-sulfur calcium silicate sulfate corrosion inhibitor and a preparation method, selecting barium salt or lead salt as an ion curing agent. For example, CN 102351456A discloses a carbon-sulfur calcium silicate sulfate corrosion inhibitor and its preparation method and application, selecting barium chloride, barium hydroxide or barium nitrate as an inhibitor, and using a superimposed packaging technology process to achieve Ba 2+ The multi-stage long-term sustained release characteristics can achieve long-term improvement in the TSA damage resistance of cement-based materials; however, barium hydroxide and barium carbonate are both toxic to the human body. When used in cement-based materials, especially when the dosage is high, barium ions as heavy metal ions are harmful to the ecological environment, which is contrary to my country's current environmental protection policies.
[0005] Therefore, there is an urgent need to develop a concrete with good resistance to sulfate erosion by calcium sulfide silicate to meet the needs of its application in structures such as submarine tunnels, bridge pile foundations, and dam bottom plates. Summary of the invention
[0006] In order to solve the problem that the existing technology of optimizing the pore structure with a single mineral admixture to improve the resistance to carbon-sulfur-silicon calcium sulfate erosion is limited and easily leads to insufficient early strength, and to consume SO4 by adding barium salt 2- In order to improve the toxic side effects and environmental damage of the corrosion resistance of calcium sulfide calcium siltstone sulfate, the inventors of the present invention provide a concrete resistant to the corrosion of calcium sulfide calcium siltstone sulfate and a preparation method thereof based on the long-term research on concrete anti-corrosion technology and the risk of corrosion by calcium sulfide calcium siltstone sulfate. The concrete realizes the systematic corrosion resistance technology of "resistance-delay-delay" by rationally compounding dense-hydrophobic materials, anionic layered compounds and fibers, and improves the ability of concrete to resist the corrosion of calcium sulfide calcium siltstone sulfate.
[0007] The present invention specifically adopts the following technical solutions:
[0008] A concrete resistant to erosion by calcite-type sulfates, comprising the following components per cubic meter of the concrete mix ratio:
[0009]
[0010]
[0011] The water-cement ratio of the concrete is 0.33-0.45, the mass of the calcined anionic layered compound accounts for 1%-2% of the total mass of the cement in the concrete, and the mass of the fiber accounts for 0.1%-1.0% of the concrete, preferably 0.2%-0.4%.
[0012] Among them, the dense-hydrophobic component is to ensure that the water absorption rate of the concrete after addition is no more than 1.2% in 30 minutes; Concrete corrosion inhibitor.
[0013] The calcined anionic layered compound is selected from at least one of calcined MgAl-LDHs and CaAl-LDHs. MgAl-LDHs and CaAl-LDHs can be obtained by commercial means, or synthesized by coprecipitation or hydrothermal synthesis, and then calcined at a temperature range of 400°C to 600°C for 4h to 6h, and naturally cooled to room temperature to obtain the calcined anionic layered compound.
[0014] The fiber is selected from at least one of modified polypropylene fiber and steel fiber; the fiber length is controlled to be 30 mm to 50 mm, and the aspect ratio is 40:1 to 80:1.
[0015] The auxiliary cementitious material is a mixture of fly ash, mineral powder or metakaolin, and the fly ash is controlled to account for 20% to 30% of the auxiliary cementitious material.
[0016] Preferably, the fly ash is selected from Grade I fly ash, the mineral powder is selected from granulated blast furnace slag powder of Grade S90 or above, and the metakaolin is selected from granulated blast furnace slag powder with a specific surface area of 12000m 2 / kg~25000m 2 / kg of high temperature calcined kaolin.
[0017] Among them, the fine aggregate is natural river sand, and the preferred fineness modulus is 2.3 to 3.0.
[0018] Generally, the cement is selected from any one of Portland cement, ordinary Portland cement, low heat cement or sulfate-resistant cement.
[0019] Generally, the coarse aggregate can be selected from continuously graded basalt crushed stone with a particle size of 5mm to 40mm, wherein small stones with a particle size of 5mm to 20mm account for 30% to 40% of the total mass of the coarse aggregate; of course, other conventional coarse aggregates in the field that play a similar role to the above-mentioned basalt crushed stone can also be selected, which will not be described here one by one.
[0020] The above-mentioned concrete resistant to erosion by calcium sulfide calcite type sulfate provided by the present invention has the advantages that, firstly, the dense-hydrophobic material can not only make the pore surface of the concrete hydrophobic, but also adsorb on the pore surface to reduce the effective transmission cross-sectional area, so that when SO4 2- and CO3 2- When it invades the surface of concrete, it effectively blocks SO4 2- and CO3 2- Second, the use of CO3 2- or SO4 2-CO3 2- and SO4 2- This method can achieve better curing effect than simple anion exchange curing, and further enhances the CO3 2- 、SO4 2- The precipitation effect slows down the process of reacting with cement hydration products to form calcium sulfide silicate. In addition, the mineral powder and metakaolin in the auxiliary cementitious material can also participate in the reaction during cement hydration to form anionic layered compounds with hydrotalcite structure, thereby continuously exerting its effect on SO4 2- and CO3 2- The anion precipitation solidification process further slows down the SO4 2- and CO3 2- The process of reacting with cement hydration products to form calcium sulfide silicate; thirdly, some excess SO4 2- and CO3 2- It reacts with the hydration product to generate a small amount of calcium calcite, which can prolong the mechanical attenuation of concrete caused by the unbonded products produced by calcium calcite sulfate erosion through the restraining effect of the fibers with short and thick structures. The concrete is rationally compounded with multiple components to achieve systematized resistance to calcium calcite sulfate erosion through the composite effect of "resistance-delay-delay". Compared with the existing technology that uses dense pore structure or barium salt to consume SO4 2- The technology of using single method to resist carbon-sulfur-silicon calcium sulfate erosion has greatly improved the anti-erosion effect, and also avoided problems such as early strength degradation and pollution. In addition, it also adopted different measures for different stages of the entire erosion process to exert long-term anti-erosion effects in stages.
[0021] Another object of the present invention is to provide a method for preparing the above concrete resistant to sulfate attack by calcite type, comprising the following steps:
[0022] S1. The coarse aggregate, the fine aggregate and part of the fiber are fully mixed and dispersed, and then cement, auxiliary cementitious materials and calcined anionic layered compounds are added and stirred continuously, and finally the remaining fiber is added to obtain a concrete mixture;
[0023] S2. Add the dense-hydrophobic material and water to the concrete mixture respectively, vibrate it into shape, and carry out standard curing for not less than 56 days.
[0024] In step S1, the purpose of adding the fibers in batches is to ensure uniform distribution of the fibers in the concrete; generally, dry mixing is performed for no less than 30 seconds after each batch is added, which can effectively avoid fiber agglomeration.
[0025] In step S2, the water adding process is generally controlled not to exceed 30 seconds to avoid uneven mixing of concrete due to excessively long water adding time and poor concrete fluidity. DETAILED DESCRIPTION
[0026] The embodiments of the present invention are described in detail below. The implementation effects of the concrete resistant to erosion by calcite-type sulfate in the present invention include but are not limited to the embodiments, and the technicians related to the present invention can adjust the proportion of the concrete resistant to erosion by calcite-type sulfate within the applicable scope of the present invention according to the actual project.
[0027] Table 1 below lists the components of the concrete resistant to calcite sulfate attack in Examples 1 to 5.
[0028] Table 1 Composition of concrete resistant to sulfate attack by calcium sulfide calcite type in Examples 1 to 5 Unit: kg / m 3
[0029]
[0030] In Table 1 above, the water-cement ratio is calculated as: the ratio of the total mass of water and dense-hydrophobic material to the total mass of cement and auxiliary cementitious materials.
[0031] It should be noted that in the above-mentioned Examples 1 to 5, the fine aggregates are all natural river sand, the coarse aggregates are all continuously graded basalt crushed stones with a particle size of 5 mm to 40 mm, and the dense-hydrophobic materials are all from Jiangsu Subote Company. Concrete erosion inhibitor (effective solid content is 15%, density is about 1.05g / cm 3 , pH about 7.0±1.0)
[0032] In the concrete of the present invention, the specific auxiliary cementitious materials, fine aggregate types, dense-hydrophobic materials, anionic layered compounds, and fiber types and types play a vital role in resisting the attack of calcite-type sulfate. In order to demonstrate and verify the key roles of the above five components, the following comparative test was conducted.
[0033] In each embodiment in Table 1, one of the above key components is changed. The key component changes in each comparative example are shown in Table 2.
[0034] Table 2 Changes of the comparative concrete in Comparative Examples 1 to 6 compared with the concrete in Examples 1 to 5
[0035]
[0036] In order to compare the performance of the concrete in Examples 1 to 5 with Comparative Examples 1 to 6 in terms of resistance to calcite-type sulfate attack, test blocks were prepared using the following concrete preparation and curing methods.
[0037] First, the concrete mixing process.
[0038] Calculate the volume containing the surplus of the test specimen, and weigh the corresponding volume of each component material according to Table 1. First, add the coarse aggregate, fine aggregate and part of the fiber into a twin-shaft concrete mixer and stir for about 30 seconds to fully mix, then add cement, auxiliary cementitious materials, and anionic layered compounds and continue stirring for about 30 seconds to fully disperse, and finally add the remaining fiber to obtain a concrete mixture.
[0039] First add some water to the concrete mixture, add the dense-hydrophobic material, and then use the remaining water to repeatedly rinse the container containing the dense-hydrophobic material until all the water is used up. The entire water adding process should not exceed 30 seconds; continue to stir the concrete for 3 minutes.
[0040] Then, the concrete forming process begins.
[0041] Pour the fresh concrete from the mixer and vibrate it into a mold in accordance with GB / T 50080-2016 "Standard for Test Methods for Properties of Ordinary Concrete Mixtures".
[0042] Finally, concrete curing process.
[0043] After demoulding, the test block should be immediately placed in a standard curing room with a temperature of 20±2℃ and a relative humidity of more than 95% for curing for 56 days.
[0044] The concrete blocks cured to the age are subjected to electric pulse low-temperature sulfate corrosion test according to T / CECS10166-2021 "Test method for concrete resistance to low-temperature sulfate corrosion". The cathode and anode corrosion solutions should be mixed sulfate solutions, which are prepared with a mass concentration of 2.4% sodium sulfate, 0.2% calcium sulfate and 2.0% magnesium sulfate.
[0045] In view of the fact that the concrete in Examples 1 to 5 and Comparative Examples 1 to 6 has better resistance to calcite-type sulfate attack than ordinary concrete, it is specified that the concrete compressive strength loss rate, hardness loss rate and calcite content at the cathode corrosion end of the test block are tested after 150 days (using the XRD / Rietveld method).
[0046] The concrete appearance erosion damage was graded according to the method described in Reference 1 (Sotiriadis K, Nikolopoulou E, Tsivilis S. Sulfate resistance of limestone cement concrete exposed to combined chloride and sulfate environment at low temperature [J]. Cement and Concrete Composites, 2012, 34 (8): 903-910). The corresponding relationship between the assessment grade and the damage characteristics is shown in Table 3 below.
[0047] Table 3 Correspondence between assessment level and damage characteristics
[0048]
[0049] Table 4 lists the performance test results of each concrete in Examples 1 to 5 and Comparative Examples 1 to 6 against carbon-sulfur-calcite-type sulfate attack.
[0050] Table 4 Performance test of each concrete in the embodiment and comparative example against calcite sulfate erosion
[0051]
[0052]
[0053] From the test results of the performance of the concrete in Examples 1 to 5 and Comparative Examples 1 to 6 in Table 4, it can be seen that after changing the key components in the concrete, its performance of resisting the corrosion of the concrete sulfate is greatly reduced. In terms of appearance, the corrosion level of the concrete in each embodiment changes from a state of no corrosion or minimal corrosion with no obvious damage or damage at the four corners to a state of severe corrosion with the concrete surface expanding and falling off or producing mud.
[0054] Specifically, the content of carbon sulfide siliceous stone in the corrosion product of Comparative Example 1 is less varied than that of Example 1, mainly because the hydrophobic-dense material and the calcined anionic layered compound can block and solidify most of the SO4 2- and CO3 2- , and a large amount of erosion products cannot be generated; however, due to the high proportion of fly ash, the hydration rate is slow and the strength is low, so the strength decreases significantly after erosion.
[0055] Comparative Example 2 Compared with Example 2, the machine-made sand carries stone powder, which provides an internal carbon source for the erosion of carbon-sulfur-silicon calcium sulfate in a low-temperature sulfate environment. Therefore, even if there are hydrophobic-dense materials and calcined anionic layered compounds, they can hinder and solidify SO4 2- and CO3 2- , the amount of calcite produced still increases significantly. It can be seen that in the calcite-type sulfate-resistant concrete of the present invention, the coarse aggregate is not recommended to be calcium carbonate or machine-made sand fine aggregate or other conventional concrete coarse aggregate.
[0056] Comparative Example 3 Compared with Example 3, the amount of hydrophobic-compacting material used is insufficient and cannot effectively inhibit SO4 2- 、CO3 2- The transport effect leads to the invasion of a large number of corrosive ions, and the excess SO4 after saturation is solidified by the precipitation of calcined anionic layered compounds. 2- 、CO3 2- That is, it reacts with cement hydration products to form calcium sulfide silicate, and eventually a large amount of calcium sulfide silicate erosion products are generated, causing a significant reduction in the mechanical properties of concrete.
[0057] Compared with Example 4, Comparative Example 4 lacks the curing effect of calcining the anionic layered compound. 2- 、CO3 2- Relatively small, but after the invasion of SO4 2- and CO3 2- Due to the lack of ion precipitation and solidification process, it directly reacts with cement hydration products to form calcium sulfide silicate, which also leads to a large amount of calcium sulfide silicate erosion products, and the mechanical properties of concrete are greatly reduced.
[0058] Compared with Example 5, in Comparative Example 5, under the hindrance of hydrophobic-dense materials, calcined anionic layered compounds and ion precipitation solidification, the amount of calcium siliceous calcium phosphate generated is less, but because the generated calcium siliceous calcium phosphate has no bonding ability inside the concrete, the compressive strength and hardness of the concrete will be lost faster in the absence of fiber constraints.
[0059] Compared with Example 4, the anionic layered compound in Comparative Example 6 lacks calcination treatment, and the SO4 2- and CO3 2-Due to the low activity of anionic layered compounds, only part of the ions undergo the solidification process, and the remaining part continues to directly react with cement hydration products to form calcium calcite, which also leads to more calcium calcite erosion products and reduced mechanical properties of concrete. In addition, the calcination process of anionic layered compounds has a great influence on their activity and the performance of precipitated ions. When the calcination temperature is higher than 600℃, the activity of the products formed is reduced, mainly spinel, and the rehydration ability is lost; if the calcination temperature is lower than 400℃, the interlayer anions of the anionic layered compounds cannot be decomposed and released, resulting in too low activity. In addition, the calcination time needs to be controlled between 4h and 6h. If the calcination time is less than 4h, the anionic layered compounds cannot be fully converted into a highly active state, and if the time exceeds 6h, the anionic layered compounds will be completely converted into a highly active state. Prolonging the calcination time increases energy consumption, resulting in reduced efficiency of the calcination process.
[0060] The concrete resistant to erosion by calcium-sulfur-silicon-type sulfate of the present invention has flexible mix ratio, and relevant technicians can adjust the mix ratio of the concrete resistant to erosion by calcium-sulfur-silicon-type sulfate within the applicable scope of the present invention under the condition of controlling key components according to actual engineering practice.
Claims
1. A concrete resistant to calcite sulfate attack, characterized in that: The concrete mix ratio includes the following components per cubic meter: The water-binder ratio of the concrete is 0.33-0.45, the mass of the calcined anionic layered compound accounts for 1%-2% of the total mass of the glue in the concrete, and the mass of the fiber accounts for 0.1%-1.0% of the total mass of the concrete; The calcined anionic layered compound is obtained by calcining the anionic layered compound at a temperature range of 400°C to 600°C for 4h to 6h, and then naturally cooling to room temperature; The auxiliary cementitious material is a mixture of fly ash, mineral powder or metakaolin, and the fly ash accounts for 20% to 30% of the weight of the auxiliary cementitious material.
2. The concrete according to claim 1, characterized in that The anionic layered compound is selected from at least one of MgAl-LDHs and CaAl-LDHs.
3. The concrete according to claim 1 or 2, characterized in that: The dense-hydrophobic component is an admixture that ensures that the water absorption rate of the concrete after being added is no more than 1.2% within 30 minutes.
4. The concrete according to claim 3, characterized in that The dense-hydrophobic component is commercially available -TIA Concrete Erosion Inhibitor.
5. The concrete according to claim 1 or 2, characterized in that: The fly ash is Grade I fly ash, the mineral powder is granulated blast furnace slag powder above Grade S90, and the metakaolin has a specific surface area of 12000m 2 / kg~25000m 2 / kg of high temperature calcined kaolin.
6. The concrete according to claim 1 or 2, characterized in that: The fiber is selected from at least one of modified polypropylene fiber and steel fiber; and / or the fiber has a length of 30 mm to 50 mm and an aspect ratio of 40:1 to 80:
1.
7. The concrete according to claim 1 or 2, characterized in that: The fine aggregate is natural river sand.
8. The concrete according to claim 1 or 2, characterized in that: The cement is selected from any one of silicate cement, ordinary silicate cement, low-heat cement or sulfate-resistant cement; the coarse aggregate is selected from continuously graded basalt crushed stone with a particle size of 5mm to 40mm, and / or the small stones with a particle size of 5mm to 20mm in the coarse aggregate account for 30% to 40% of the total mass of the coarse aggregate.
9. A method for preparing concrete according to any one of claims 1 to 8, characterized in that: Includes steps: S1, fully mixing and dispersing the coarse aggregate, fine aggregate and part of the fiber, then adding the cement, auxiliary cementitious material, calcined anionic layered compound and continuing to stir, and finally adding the remaining fiber to obtain a concrete mixture; S2. Adding the dense-hydrophobic material and the water to the concrete mixture respectively, vibrating and shaping, and performing standard curing for not less than 56 days, thereby obtaining the concrete mixture.
Citation Information
Patent Citations
Thaumasite form sulfate attack (TSA) inhibitor, preparation method thereof and application thereof
CN102351456A
Thaumasite form of sulfate attack inhibitor and preparation method
CN107324681A
Cited By
Anti-erosion hydraulic concrete and preparation method thereof
CN120943594A
An erosion-resistant hydraulic concrete and a method for producing the same
CN120943594B
Preparation method of carbonate corrosion resistant lining concrete
CN122187430A
A method of preparing a carbonate corrosion resistant lining concrete
CN122187430B